Application and Theory of Petri Nets and Concurrency : 38th International Conference, PETRI NETS 2017, Zaragoza, Spain, June 2530, 2017, proceedings /: 38th International Conference, PETRI NETS 2017, Zaragoza, Spain, June 2530, 2017, proceedings. ([2017]) - Unknown
No abstract available